Collective Labor Rights and Income Inequality - Kerrissey, Jasmine (American Sociological Review, 2015)
This article examines the relationship between income inequality and collective labor rights, conceptualized as workers’ legal and practical ability to engage in collective activity. Although worker organization is central to explaining income inequality in industrialized democracies, worldwide comparative studies have neglected the role of class-based actors. I argue that the repression of labor rights reduces the capacity of worker organizations to effectively challenge income inequality through market and political processes in capitalist societies. Labor rights, however, are unlikely to have uniform effects across regions. This study uses unbalanced panel data for 100 developed and less developed countries from 1985 through 2002. Random- and fixed-effects models find that strong labor rights are tightly linked to lower inequality across a large range of countries, including in the Global South. Interactions between regions and labor rights suggest that the broader context in which class-based actors are embedded shapes worker organizations’ ability to reduce inequality. During the period of this study, labor rights were particularly important for mitigating inequality in the West but less so in Eastern Europe.